Small meanders of the Kuroshio Extension and associated northward spreading of warm water: Three‐vessel simultaneous observations and an eddy‐resolving ocean model simulation. Issue 7 (31st July 2016) - Kobashi, Fumiaki; Onikata, Yukino; Iwasaka, Naoto; Kawai, Yoshimi; Oka, Eitarou; Uehara, Kazuyuki; Ito, Shin‐ichi; Odamaki, Minoru; Sasaki, Hideharu
Abstract: Small meanders of the Kuroshio Extension (KE) were examined in the three vessel simultaneous observations carried out across the KE along 143°E between 2 and 7 July 2012 and the hindcast simulation by a high‐resolution ocean model for the Earth Simulator (OFES). The observations captured the crest of the small meander that passed 143°E. Behind the meander crest, the meander showed the northward separation of the front from the meandering jet. It was suggested that the meander spread the low‐density KE water to the north above the main pycnocline there. The OFES showed similar characteristics of small meanders. We focused on three major small meanders. In the upstream KE region west of 143°E, these meanders were subject to northeastward ageostrophic advection, by which the low‐density KE water was carried to the north and their fronts moved away from the KE jet above the main pycnocline. This resulted in the KE water and the front extending to the west behind the crest of the downstream‐propagating meanders. This feature was particularly obvious for the two cases of the meander and was consistent with the observations. The displaced front formed a shallow geostrophic jet to the north of the main KE jet, which induced geostrophic advection along the jet and advected the front further northward and downstream near the crest of the meandering front. The KE water spread by the small meanders then mostly evolved into warm core rings or warm streamers. Key Points: Three vessel simultaneous observations captured a small meander of the Kuroshio Extension Small meanders of the Kuroshio Extension spread warm water to the north Ageostrophic flow plays the important role in spreading the Kuroshio Extension water